Apologies and moral repair : rights, duties, and corrective justice - Cohen, Andrew I. (New York, NY : Routledge, 2020)
"This book argues that justice often governs apologies. Drawing on examples from literature, politics, and current events, Cohen presents a theory of apology as corrective offers. Many leading accounts of apology say much about what apologies do and why they are important. They stop short of exploring whether and how justice governs apologies. Cohen argues that corrective justice may require apologies as offers of reparation. Individuals, corporations, and states may then have rights or duties regarding apology. Exercising rights to apology or fulfilling duties to provide them are ways of holding one another mutually accountable. By casting rights and duties of apology as justifiable to free and equal persons, the book advances conversations about how liberalism may respond to historic injustice. Apologies and Moral Repair will be of interest to scholars and advanced students in ethics, political philosophy, and social philosophy"--
OCLC-licensed vendor bibliographic record.
Keywords: Apologizing; Ethics; PHILOSOPHY / Ethics & Moral Philosophy